The Influence of Audit Tenure, Audit Fee, and Institutional Ownership on Audit Delay: Study of Companies in Various Industrial Sectors Listed on The Indonesian Stock Exchange 2018-2022 - Alfaruq, Zakiyuddin Abdul Malik; Maulana, Ryan; Fadjar, Achmad (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
ABSTRACT   Purpose: This research aims to analyze the influence of audit tenure, audit fee, and institutional ownership on audit delay.Design/methodology: To do this research, the method chosen is quantitative. The sample used included 21 companies from various industries listed on the Indonesian Stock Exchange and data collected over five years, from 2018 to 2022. The logistic regression test is the analysis used.. Findings: The results showed that the probability values of audit tenure, audit fees, and institutional ownership were less than the significance level of 0.05, suggesting that the increase and decrease in the number of audits in tenure, audit fees, and institutional ownership were not large enough to indicate a significant influence on the audit delay proposed as a hypothesis.Practical implications: The author organized the diverse factors and findings inside the structured literature review, while this study, which focuses on Institutional Ownership and board governance, provides valuable insights into earlier studies. The writers guide academics, regulatory agencies, and company practices in this corporate governance topic.Originality/Value: This research is relatively new because it uses varying audit fees and various industrial sectors, which include various industrial sectors, so that the research results can be more acceptable.